Vision problems in people over 50 years old in Peru: A population-based study - Cruzado-Sanchez, Deivy (2022)
Objective: To evaluate the history of cataract and vision problems in people over 50 years of age in Peru. Methods: Secondary database analysis of the Demographic and Family Health Survey (ENDES) 2016. We included 7970 adults over 50 years of age. We evaluated the indicators of interest at the national and regional level. Likewise, we analyzed factors related to these events using a multivariate Poisson model. Results: 13.6% (95% CI: 12.8-14.3%) had a history of cataract, 20.4% (95%CI: 19.5-21.3%) had long-distance vision problems. (LDVP) and 29.4% (95%CI: 28.4-30.4%) of short-distance vision problems (SDVP). In the multivariate model, we observed that people with a history of high blood pressure, a history of diabetes, and older age groups were significantly more likely to report a history of cataracts and vision problems. We also observed that people with a better economic status had a lower frequency of LDVP and SDVP. Conclusion: The history of cataract and vision problems in the studied population vary according to sociodemographic and geographic characteristics. The identification of factors related to these events of interest allows us to propose better interventions to control these problems.